Nurturing Prospective STEM Teachers' Critical Thinking Skill through Virtual Simulation-Assisted Remote Inquiry in Fourier Transform Courses - Bilad, Muhammad Roil; Anwar, Kaspul; Hayati, Susruhiyatun (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Alignment of inquiry learning has embarked on remote inquiry as a replacement for face-to-face inquiry. On the other hand, the current technological developments bring opportunities to use it as a learning resource to support critical thinking. The current study explores the impact of virtual simulation-assisted remote inquiry in Fourier transform courses on prospective STEM teachers' (PST) critical thinking (CT) skills. The experimental design employed a randomized pretest-posttest control group was employed. Two groups of samples were randomized: the experimental group, n = 30, and the control group, n = 30. The treatment of learning was different in each group. The experimental group was conducted by virtual simulation-assisted remote inquiry, while the control group was conducted by online learning without inquiry and simulation. The measured CT skills aspects included analytical, inference, evaluation, and decision-making measured by an essay test instrument. The results were then analyzed descriptively and statistically. The results confirm that the virtual simulation-assisted remote inquiry significantly improved PST CT in Fourier transform courses. The virtual simulation-assisted remote inquiry learning was better than courses with online learning without inquiry and simulation. The virtual simulation-assisted remote inquiry provided conceptual formation and application of concepts. It strengthened the opportunities for the PSTs to train their CT skills.